Slow Rupture, Long Rise Times, and Multi‐Fault Geometry: The 2020 M6.4 Southwestern Puerto Rico Mainshock - M. M. Solares‐Colón; D. E. Goldberg; D. Melgar; E. A. Vanacore; V. J. Sahakian; W. L. Yeck; F. Hernández; A. M. López‐Venegas (Geophysical Research Letters)
Abstract The M6.4 mainshock of the southwestern Puerto Rico seismic sequence on 7 January 2020, was one of the most impactful modern earthquakes in the northeastern Caribbean. Due to its offshore location and complex aftershock distribution, its source kinematics remain poorly constrained. This active sequence illuminated a complex set of previously unrecognized structures that indicate multiple causative faults may have slipped during its rupture. Here, we utilize seismic and geodetic observations to enhance model resolution, estimate the finite slip of the mainshock, and test a multi‐segment, geologically realistic fault geometry. Our refined model finds a lower rupture velocity and longer rise times than typical for an event of this magnitude. This indicates a slow‐evolving rupture process that resembles characteristics of a tsunami earthquake. Although this normal/strike‐slip faulting event was not tsunamigenic, these qualities, if pervasive for this region, have important implications for future seismic monitoring and hazards in southwestern Puerto Rico.